Peningkatan Kompetensi Guru MA Al Ikhlas Berbah Melalui Pelatihan Microlearning dengan Google Sites - Kristina Uskenat; Tutik Yuliatun (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The implementation of technology-based learning is currently increasingly developing, so teachers need to increase their competence in developing learning media. This community service activity is carried out through training methods. This training activity aims to increase teacher competency in learning through microlearning training with Google Sites. The target of this activity is the MA Al Ikhlas Berbah teacher. This microlearning training with Google sites was attended by 17 MA Al Ikhlas Berbah teachers and was carried out from June to July 2023 with 5 stages of activities including 1) surveys and permits in the form of observing learning needs and implementation; 2) socialization includes explanation of planned training activities; 3) training related to the explanation and practice of microlearning with Google sites; 4) monitoring and assisting in the creation of microlearning-based learning media using Google Sites and 5) evaluating the implementation of training. The results of this service in the form of training activities are increasing the competency of MA Al Ikhlas Berbah teachers through microlearning training with Google sites which can be seen from the pretest and posttest results which have increased to 97.75% in understanding the implementation of microlearning in learning.